2021
DOI: 10.1039/d0md00282h
|View full text |Cite
|
Sign up to set email alerts
|

Identification of LASSBio-1945 as an inhibitor of SARS-CoV-2 main protease (MPRO) through in silico screening supported by molecular docking and a fragment-based pharmacophore model

Abstract: A SARS-CoV-2 main protease (MPRO) inhibitor was discovered employing molecular docking and a fragment-based pharmacophore model as virtual screening strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…The two residues with the highest interaction frequencies from this pocket were M49 (65%) and H164 (58%) which formed hydrophobic and weak hydrogen bond interactions, while M165 (47%) and Q189 (43%) interacted mainly by hydrophobic contacts with the ligands (Figure 3B and 4A). The high frequency of interactions with S1 and S2 residues showed that most of the ligands fill one or both pockets, conserving a more polar profile for S1, whereas the S2 retained a more aromatic and aliphatic profile as observed previously with the SARS-CoV Mpro [118] and in other studies with SARS-CoV-2 Mpro [119,120].…”
Section: Available Mpro Structures Show Conserved Conformation Protein-ligand Interactions and Location Of Waters Moleculessupporting
confidence: 77%
“…The two residues with the highest interaction frequencies from this pocket were M49 (65%) and H164 (58%) which formed hydrophobic and weak hydrogen bond interactions, while M165 (47%) and Q189 (43%) interacted mainly by hydrophobic contacts with the ligands (Figure 3B and 4A). The high frequency of interactions with S1 and S2 residues showed that most of the ligands fill one or both pockets, conserving a more polar profile for S1, whereas the S2 retained a more aromatic and aliphatic profile as observed previously with the SARS-CoV Mpro [118] and in other studies with SARS-CoV-2 Mpro [119,120].…”
Section: Available Mpro Structures Show Conserved Conformation Protein-ligand Interactions and Location Of Waters Moleculessupporting
confidence: 77%
“…This study yielded a significant number of novel chemotypes, suitable for future medicinal chemistry optimization, but also yielded one of the most potent Mpro inhibitors that emerged from only molecular docking 8,[52][53][54] .…”
Section: Discussionmentioning
confidence: 99%
“…Here, His 41 forms hydrophobic interactions and His 163 donates hydrogen bonds whereas Glu 166 serves as a hydrogen bond donor or acceptor. A 3-amino-pyridinyl moiety found in several fragments including 1, TRY-UNI-714a760b-6, and EDG-MED-0da5ad92–2 was also found to show effective inhibitory properties with respective IC 50 values of 24.57 and 53.72 μM ( Franco et al, 2020 ). An amino acid decomposition analysis together with a molecular dynamic simulation was also applied when looking for SARS-CoV-2 M pro inhibitors where hydrogen bonds and hydrophobic interactions were found to hold the complex ( Choudhury, 2020 ).…”
Section: Potential Inhibitors Of Sars-cov-2 M Promentioning
confidence: 99%